Implementasi Kebijakan Pendidikan Karakter di MTsN 3 Palas - Asma Yulina; M. Hady Al Asy Ary; Muhammad Iqbal; Nailan Nikmah Siregar; Sukriani Hasibuan; Tri Wulan Hasibuan (Departement of Mathematics Education, 2023)
This study aims to describe the implementation of character education policies at MTsN 3 PALAS, supporting factors, inhibiting factors, and the impacts and solutions of implementing character education policies for students. This research uses a qualitative approach with descriptive methods. With the research subject of the principal, homeroom teacher and students. Supported by data collection techniques using the method of observation, observation and interviews as well as documentation. The data analysis used is data reduction, data presentation, and conclusion/verification. The results of this study indicate that: 1) the implementation of character education policies at MTsN 3 PALAS is carried out by school members by implementing them in the teaching and learning process, 2) supporting factors, namely good cooperation between school members, student awareness, a conducive environment and activities that programmed. 3) The inhibiting factors are the teacher's limitations in carrying out character education, the lack of parental supervision of children 4) the solution to the obstacles is an individual approach to students and the impact of implementing this character education policy is to create self-confidence and discipline.